A Note on L.C.Q.K. Manifolds. Issue 2 (2nd July 2020) - Choudhary, Majid Ali
Abstract: L.c.q.K. manifolds were investigated by ([4], [7], [6], [8]) and antiinvariant Riemannian submersion was studied in ([10], [1]). The present note aims to work on anti-invariant and Lagrangian Riemannian submersion of locally conformal quaternion Kaehler manifolds. Further, the geometry of foliation is discussed and some decomposition results for such submersions are obtained.